An experiment in first language acquisition : a case study of a Malaysian Indian child acquiring English - Cheong, Thye Yuen (Universiti sains malaysia, 1983)
This academic exercise has been written in five chapters. Chapter one, the introduction, sets out to give the reader a brief outline on the aim of this study, the procedure used for data collection and an introductory account on the methodology used.Chapter two provides a review of the literature of child language acquisition commencing from sources of interest in child language learning to the earliest stage - babbling,to the language comprehension stage (18 months). The chapter ends with a view of theories of first language acquisition.